2021
DOI: 10.3390/app11083537
|View full text |Cite
|
Sign up to set email alerts
|

The Soil Chemical Properties Influencing the Oribatid Mite (Acari; Oribatida) Abundance and Diversity in Coal Ash Basin Vicinage

Abstract: The samples of two technogenic sediments (MOS, coal ash sediment; MOD, a mixture of ash and natural soil) and two natural soils (MOM, meadow; MOF—forest; both Cambisol Dystric) in the vicinage of the coal ash basin were studied. We evaluated risk element concentrations and select-ed chemical and microbiological parameters to determine their influence on the community structure of Oribatida. High concentrations of various toxic elements, alkaline pH, and low hu-midity negatively affected the abundance of oribat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
6
0
1
Order By: Relevance
“…Studies on Mesostigmata communities from natural ecosystems revealed that mites were reported as most abundant in soils with low pH (Kamczyc et al, 2018; Manu et al, 2016; Meehan et al, 2018). Feketeová et al (2021) obtained similar studies on mite abundance and diversity in the vicinity of a coal ash basin. Some research revealed that soil acidity is unlikely to affect mite communities directly because species can grow on very acidic soils (Feketeová et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Studies on Mesostigmata communities from natural ecosystems revealed that mites were reported as most abundant in soils with low pH (Kamczyc et al, 2018; Manu et al, 2016; Meehan et al, 2018). Feketeová et al (2021) obtained similar studies on mite abundance and diversity in the vicinity of a coal ash basin. Some research revealed that soil acidity is unlikely to affect mite communities directly because species can grow on very acidic soils (Feketeová et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Soil acidity and forest type were significant factors for the abundance and community structure of soil mites (Kamczyc et al, 2018; Maraun & Scheu, 2000). Feketeová et al (2021) detected negative correlations between the C/N ratio and abundance and diversity of oribatid mites in the vicinity of a coal ash basin, which suggests that this factor may also be important for Mesostigmata. The OM content was lower in ash pond sediment and a mixture of ash and natural soils, compared to forests.…”
Section: Discussionmentioning
confidence: 99%
“…The species T. sarekensis is an opportunistic herbofungivore and is widely distributed in different European and North American habitats (Coleman et al 2018 ). It is encountered in cultivated plots (Rockett 1986 ), but also at highly metal-contaminated sites (Feketeová et al 2021 ; Skubala et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous fertilization cannot explain the significant presence of the two main species. The Tectocepheidae has been classified as the most insensitive group to environmental destruction (Rockett 1986 ) or strong disturbances (Zaitsev et al 2002 ), Feketeová et al ( 2021 ) describe Z. acutirostris as a suitable indicator of improper human intervention in an ecosystem. As an example, it has been described that under stress induced by organophosphate or chlorinated hydrocarbon products, its presence was enhanced (Behan-Pelletier 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are not favourable for soil organisms and therefore the number of species and the number of individuals decrease. One species with a wide range of tolerance that can tolerate high concentrations heavy metals is Tectocepheus velatus sarekensis, which occurs even in such unfavourable soils (Technosol) (Feketeová et al, 2021). It is an opportunistic, r-strategist species that reproduces by parthenogenesis and is able to colonize such areas (Błoszyk et al, 2004).…”
Section: Ecological Indicationmentioning
confidence: 99%